Propriedades físicas e de adesão bacteriana de uma resina composta fotopolimerizável modificada com nanopartículas de prata - Neves, Patrícia Bolzan Agnelli das (Universidade Federal de São Carlos, 2014)
The evaluation of new materials and biomaterials modified with silver nanoparticles is a line of research that has been gaining strength in various knowledge areas including dentistry. Even considering international scientific publications, however, there are still few studies evaluating dental restoration materials that are modified with silver nanoparticles. Proposal: this study aimed to compare a photopolymerizable composite resin modified with an antimicrobial silver nanoparticle additive (an experimental resin), with the photopolymerizable composite resin in its unmodified form (a commercially available dental restoration material), by evaluating the in vitro antibacterial properties and also some of the primary physical properties of the resin. Methodology: composite resin disks were made for three experimental groups: unmodified resin (control group) and modified resin with different silver nanoparticle concentrations: 0.3% and 0.6% wt (groups 1 and 2). The antibacterial activity on the surface of the samples was evaluated by in vitro growth of of Streptococcus mutans and Lactobacillus acidophilus biofilms in a 20% sucrose medium, which is followed by counting the viable cells from the biofilms through serial dilutions after three incubation periods - 1, 4 and 7 days (n = 9). Optical transmittance was tested to measure the percentage of transmittance in the samples (n = 9). The surface roughness was evaluated using Atomic Force Microscopy (n = 9). The colour of the samples and the colour difference between the groups was measured in a colorimetry test according to the CIELab system. The presence of silver in the nanoparticle additive was analysed using X-Ray Fluorescence Spectroscopy. The quality of the dispersion and distribution of silver on the samples was analysed using Transmission Microscopy. The liberation of silver in artificial saliva was also evaluated in vitro after three incubation periods (60, 120 and 210 days) with agitation of the samples, using the Inductively Coupled Plasma Optical Emission Spectroscopy technique. Results: for the three incubation times, the number of viable cells was statistically lower in groups 1 and 2 than in the control group (p < 0.05), and groups 1 and 2 were not statistically different (p > 0.05) for the two bacterial species (ANOVA Two way/Tukey). There was no significant difference in optical transmittance between group 1 and the control (p > 0.05), and group 2 had a lower transmittance value than the other groups (p < 0.05) (ANOVA/Tukey). The analysis of the values of the arithmetic roughness, which was obtained using the NanoScope software, showed that there was no significant difference in surface roughness between the three groups (p > 0.05) (ANOVA/Tukey). From the measurements of the colours, the total colour difference (ΔE) between all of the groups was higher than 1 (the minimum value that represents a colour alteration perceptible to human vision) and lower than 3,3 (critical ΔE). The presence of silver in the nanoparticle additive was confirmed in the X-Ray Fluorescence test. Microscopic analysis showed good distribution of silver for groups 1 and 2 (with silver in the four quadrants of the regions analysed). The dispersion was better for group 1 than for group 2 (which showed a higher number of particle clusters). After the three incubation times, silver was not detected in the artificial saliva for the three groups or; if it was present, the concentration was below the limit of detection for this technique (< 0.02 mg/L). Conclusions: the antibacterial property on the surfaces of the experimental resins was verified for the two cariogenic bacteria considered. Furthermore, the addition of silver did not cause negative alterations to the resin modified with the lower concentration of nanoparticles, which makes the continuation of this study possible and valuable.
Keywords: Propriedades físicas; Adesão bacteriana; Resina composta; Nanopartículas de prata; Streptococcus mutans; Biotecnologia; Physical properties; Bacterial adhesion; Composite resin; Silver nanoparticles; Lactobacillus acidophilus; OUTROS